Subclinical peripheral atherosclerosis in patients with chronic pulmonary disease: the role of psychological distress predisposition - A. N. Sumin; E. V. Nedoseikina; O. G. Arkhipov (Российский кардиологический журнал, 2013)
Aim. To assess the association between Type D personality and the severity of subclinical peripheral atherosclerosis in patients with chronic pulmonary disease. Material and methods. In total, 134 patients with chronic pulmonary disease (104 men and 30 women; mean age 58,9±0,5 years, range 44–78 years), who participated in the rehabilitation programme at the Topaz Rehabilitation Centre, were examined. All participants underwent spirometry, 6-minute walk test, and clinical and biochemical blood assays. Type D personality was diagnosed using the DS-14 instrument. Colour duplex ultrasound of carotid arteries and leg arteries was used for the assessment of intima-media thickness and ankle-brachial index (ABI). All patients were divided into two groups: with pathologic ABI (<0,90 or >1,40; n=28) and with normal ABI (0,9–1,40; n=106). Results. Both groups were similar by the spirometry results and 6-minute walk test distance (481±16 and 502±8 m, respectively; p=0,217). The DS-14 levels of negative affect were similarly high in both groups (11,8±0,8 and 10,4±0,5; p=0,209); however, in patients with pathologic ABI, the levels of social inhibition were significantly higher (12,4±0,8) than in patients with normal ABI (9,9±0,6; p=0,033). The prevalence of Type D personality was significantly higher (67,9%) in patients with pathologic ABI, compared to their peers with normal ABI (36,8%; p<0,0001). In multilevel logistic regression analyses, only age, Type D personality, and blood leukocyte count were independent predictors of pathologic ABI. Conclusion. In the examined patients with chronic pulmonary disease, 21% had subclinical peripheral atherosclerosis. Patients with pathologic ABI were older and had higher blood levels of total cholesterol, triglycerides, and leukocytes, higher levels of intima-media thickness and social inhibition, and a higher prevalence of Type D personality. The assessment of psychological distress predisposition and its correction could play in important role in the cardiovascular prevention among patients with chronic pulmonary disease.